Efficacy of targeting bone-specific GIP receptor in ovariectomy-induced bone loss. Issue 2 (November 2018) - Mabilleau, Guillaume; Gobron, Benoit; Mieczkowska, Aleksandra; Perrot, Rodolphe; Chappard, Daniel
Abstract : Glucose-dependent insulinotropic polypeptide (GIP) has been recognized in the last decade as an important contributor of bone remodelling and is necessary for optimal bone quality. However, GIP receptors are expressed in several tissues in the body and little is known about the direct vs indirect effects of GIP on bone remodelling and quality. The aims of the present study were to validate two new GIP analogues, called [d -Ala 2 ]-GIP-Tag and [d -Ala 2 ]-GIP1–30, which specifically target either bone or whole-body GIP receptors, respectively; and to ascertain the beneficial effects of GIP therapy on bone in a mouse model of ovariectomy-induced bone loss. Both GIP analogues exhibited similar binding capacities at the GIP receptor and intracellular responses as full-length GIP1–42 . Furthermore, only [d -Ala 2 ]-GIP-Tag, but not [d -Ala 2 ]-GIP1–30, was undoubtedly found exclusively in the bone matrix and released at acidic pH. In ovariectomized animals, [d -Ala 2 ]-GIP1–30 but not [d -Ala 2 ]-GIP-Tag ameliorated bone stiffness at the same magnitude than alendronate treatment. Only [d -Ala 2 ]-GIP1–30 treatment led to significant ameliorations in cortical microarchitecture. Although alendronate treatment increased the hardness of the bone matrix and the type B carbonate substitution in the hydroxyapatite crystals, none of the GIP analogues modified bone matrix composition. Interestingly, in ovariectomy-induced bone loss, [d -Ala 2 ]-GIP-Tag failed to alter bone strength, microarchitecture and bone matrix composition. Overall, this study shows that the use of a GIP analogue that target whole-body GIP receptors might be useful to improve bone strength in ovariectomized animals.